Effectiveness of the Positive deviance and parent facilitator training strategies on the nutritional status of children and youth with cerebral palsy: A quasi-randomised trial with a factorial design. - Lukia Hamid Namaganda; John Ssenkusu; Asige Elizabeth; Carin Andrews; Angelina Kakooza Mwesige; Fred Wabwire Mangen; Hans Forssberg (PLOS Global Public Health)
High malnutrition among children with CP in low-income countries underscores the need for community-based nutrition strategies. This study aimed to describe the effectiveness of two caregiver-led interventions including, the positive deviance (PD) and the parent facilitator training (PFT) interventions on malnutrition among children and youth (C&Y) with CP in rural Eastern Uganda. This was a 2x2 factorial quasi-randomized trial among 124 pairs of caregiver-malnourished C&Y with CP aged 2-24 years, at the Iganga Mayuge Health and Demographic Surveillance Site (IMHDSS) in Eastern Uganda. Outcome measures included three months change in weight gain, Weight for-age-z scores and Body Mass Index for-age-z scores. Change in weight status was modelled in a multiple linear regression adjusting for baseline characteristics. Non-factorial analysis was used to determine the effect of combining both interventions on weight status. The interaction effect between PD and PFT was not statistically significant (P > 0.05). Those who received the PD intervention significantly gained more weight by 520g (adjusted coefficient = 0.52, 95%CI 0.16,0.88, p = 0.005) and improved their BMI for age z-scores (adjusted coefficient = 0.65, 95% CI 0.35,0.94, P < 0.01) than those who did not, while those who received PFT significantly improved their Weight for Age z-scores (adjusted coefficient = 0.42,95%CI 0.14,0.56, p = 0.006). Non-factorial analysis revealed a significant higher weight gain (770g) and improved BMI for age z-scores among those who received both interventions (adjusted coefficient = 0.77, 95%CI 0.22.1.37, p = 0.009). The PD alone or combined with PFT interventions improves weight status better than the PFT intervention alone. The PD and PFT caregiver-led strategies should be merged into existing community-based nutrition programs to reduce the high burden of malnutrition among C&Y with CP in low-income settings.